E-learning - an interventional element of the PRiVENT project to improve weaning expertise - Michels-Zetsche, Julia D.; Schubert-Haack, Janina; Tanck, Katrin; Neetz, Benjamin; Iberl, Gabriele; Müller, Michael; Kempa, Axel; Joves, Biljana; Rheinhold, Andreas; Ghiani, Alessandro; Tsitouras, Konstantinos; Schneider, Armin; et al. (BMC medical education, 2024)
PRiVENT (PRevention of invasive VENTilation) is an evaluation of a bundle of interventions aimed at the prevention of long-term invasive mechanical ventilation. One of these elements is an e-learning course for healthcare professionals to improve weaning expertise. The aim of our analysis is to examine the implementation of the course in cooperating intensive care units.
The PRiVENT-Study Group: Franziska Christina Trudzinski, Julia Dorothea Michels-Zetsche, Beatrice Müller, Jan Meis, Martina Bentner, Thomas Fleischhhauer, Johanna Forstner, Gerhard Fuchs, Nicola Litke, Markus Qreini, Selina von Schumann, Noemi Sturm, Aline Weis, Michel Wensing, Thomas Grobe, Anja Klingenberg, Alex Kempa, Ahmed Ehab, Claus Neurohr, Nina Lutz, Swenja Walcher, Joanna Paderewska, Selina Briese, Joachim Sugg, Susanne Hirschmann, Christa Straub, Claude Jabbour, Michael Hahn, Jörg Krebs, Peter-Tobias Graf, Petra Denzer, Mascha O. Fiedler, Miriane Bomeken, Sebastian Stier, Tom Terboven, Uta Merle, Jens Regula, Jens Müller, Ute Oltmanns, Marcus Hennersdorf, Neslihan Satir, Mathias Borst, Brigitte Mayer, Wolfgang Reikow, Markus Kredel, Patrick Keppeler, Konstantin Frey, Holger Wolff, Florian Seidlitz, Stefanie Bientzle, Boris Nohé, Sebastian Allgäuer, Alexej Schöpp, Christoph Schlegel, Imke Hübner, Andrezj Kuzniar, Helene Häberle, Reimer Riessen, Benjamin Schempf, Ingo Rebenschütz, Andreas Straub, Marc Kollum, Markus Winter, Paul Hartveg, Andreas Junginger, Helmut Beck, Mathias Vogel
Online veröffentlicht: 19. April 2024
Gesehen am 25.09.2024